A novel 3D optical method for measuring and evaluating springback in sheet metal forming process. (October 2016) - Zhang, Dehai; Li, Yanqin; Liu, Jianxiu; Xie, Guizhong; Su, Erwei
Highlights: 3D optical method for measuring and evaluating the springback. Evaluation index S consists of a 3D springback value w and its vectors along x, y and z directions. Point cloud obtained using photogrammetry and surface scanning systems. A cutting line for the point cloud or CAD model obtained in Geomagic Qualify. Springback calculated as the difference between any two corresponding key points in cutting. Abstract: A novel 3D optical method for measuring and evaluating the springback in sheet metal forming is presented and its principle, program and steps are studied. The optical method includes a measuring method and evaluation indexes. The point cloud, obtained using photogrammetry and surface scanning systems, is used as the workpiece shape after springback. The original mould is regarded as the CAD model before springback. The point cloud and CAD model are aligned in Geomagic Qualify. A cutting line for the point cloud or CAD model can be obtained at any point in any direction of their cross sections. The springback is calculated as the difference between any two corresponding key points on the two cutting lines. The evaluation index S consists of a 3D springback value w and its vectors along x, y and z directions. Feasibility of the optical method is verified by using a refrigerator door shell.